Answer:
m = 4
Step-by-step explanation:
Given
- 8 + 6m =
(4m + 16) ← distribute parenthesis
- 8 + 6m = 2m + 8 ( subtract 2m from both sides )
- 8 + 4m = 8 ( add 8 to both sides )
4m = 16 ( divide both sides by 4 )
m = 4
Answer:
a) What is the amount off the original price?
= $8.4
b) What is the new price for the pair of shoes?
= $33.6
Step-by-step explanation:
a) What is the amount off the original price?
We are told that:
The sale price is 20% off the original price.
Original price = $42
Hence:
$42 × 20%
$42 × 20/100
= $8.4
b) What is the new price for the pair of shoes?
The new price =
0riginal price - Amount off the original price
= $42 - $8.4
= $33.6
The original price = $33.6
Answer:
1. 54 and 9/20 km
2. 80 mm
3. 1.142 mi
4.0.83333 cm
Step-by-step explanation:
Do them all by the butterfly method.
Answer:
f(x) = x - 3
Step-by-step explanation:
y = mx + b
first let's find b, the y-intercept
based on the graph, the y-intercept is (0,-3), so b = -3
immediately, we can eliminate f(x) = 3 - x and f(x) = -3x
comment any questions pls
Answer:
Step-by-step explanation:
A system of linear equations is one which may be written in the form
a11x1 + a12x2 + · · · + a1nxn = b1 (1)
a21x1 + a22x2 + · · · + a2nxn = b2 (2)
.
am1x1 + am2x2 + · · · + amnxn = bm (m)
Here, all of the coefficients aij and all of the right hand sides bi are assumed to be known constants. All of the
xi
’s are assumed to be unknowns, that we are to solve for. Note that every left hand side is a sum of terms of
the form constant × x
Solving Linear Systems of Equations
We now introduce, by way of several examples, the systematic procedure for solving systems of linear
equations.
Here is a system of three equations in three unknowns.
x1+ x2 + x3 = 4 (1)
x1+ 2x2 + 3x3 = 9 (2)
2x1+ 3x2 + x3 = 7 (3)
We can reduce the system down to two equations in two unknowns by using the first equation to solve for x1
in terms of x2 and x3
x1 = 4 − x2 − x3 (1’)
1
and substituting this solution into the remaining two equations
(2) (4 − x2 − x3) + 2x2+3x3 = 9 =⇒ x2+2x3 = 5
(3) 2(4 − x2 − x3) + 3x2+ x3 = 7 =⇒ x2− x3 = −1